Influence of metal nanocarboxylates and different water supply conditions on efficiency of soybean-rhizobial symbiotic systems - Kots, S. Y.; Rybachenko, L. I.; Mamenko, T. P.; Kukol, K. P.; Pukhtaievych, P. P.; Rybachenko, O. R. (Regulatory Mechanisms in Biosystems, 2021)
Insufficient water supply is one of the main factors that significantly reduce the activity of nitrogen fixation by legume-rhizobial symbiotic systems. That is why comprehensive research on aspects of their resistance to water stress and the search for scientifically substantiated ways to improve the existing ones and develop modern, competitive technologies of growing legumes in arid conditions are becoming especially relevant. The aim of the work was to investigate the processes of formation and functioning of soybean-rhizobial symbiotic systems developed under conditions of different water supply and influence of nanocarboxylates of cobalt, ferum, germanium, chromium, сuprum and molybdenum. The nanoparticles of specified metal nanocarboxylates were used as components of the inoculation suspension of rhizobia of Tn5 mutant B1-20 for soybean seed treatment. A model drought lasting 14 days was created by controlled irrigation. Microbiological and physiological research methods were used in the study. We determined that insufficient water supply caused a significant decrease in the nodulation potential of rhizobia and the intensity of molecular nitrogen fixation by symbiotic systems formed with the participation of soybean plants and nodule bacteria without adding these metal nanocarboxylates to the inoculation suspension. Application of most of the metal nanocarboxylates used as components of the inoculation suspension mitigated the negative impact of stress on the investigated parameters. The study revealed the stimulating effect of cobaltnanocarboxylate on the activity of molecular nitrogen fixation, which was more pronounced in the conditions of insufficient water supply. Symbiotic soybean systems formed with the participation of nodule bacteria containing germaniumcarboxylate nanoparticles were proved to be the least sensitive to the negative impact of insufficient water supply. This was indicated by high rates of nodulation and nitrogen-fixing activity compared with other studied symbiotic systems. We confirmed that the addition of chromium nanocarboxylate to the inoculation suspension of rhizobia provided the highest rates of nodulation and nitrogen-fixing activity of soybean root nodules under optimal growing conditions and, at the same time, had no noticeable positive effect under water stress. We determined that сuprum and molybdenum nanocarboxylates, as components of the inoculation suspension, regardless of the water supply level, had a less notable positive effect on the processes of nodule formation and nitrogen fixation, and in some cases even led to a decrease in the investigated values for control plants. Thus, the study demonstrated that the use of germanium, cobalt and ferum nanocarboxylates as components of the bacterial suspension helped to increase the adaptation of the formed legume-rhizobial symbiotic systems to water stress, as evidenced by the maximum indexes of nodulation and molecular nitrogen fixation in the context of insufficient water supply and recovery of their level to optimal after the stress influence had ended. Based on the results, it was concluded that inoculation of seeds by the complex bacterial preparations made on the basis of Bradyrhizobium japonicum B1-20 with a content of germanium, cobalt and ferum nanocarboxylates in the concentration of 1:1000 can become one of the important means in soybean growing technologies of increasing the nitrogen-fixing potential and resistance of plants to insufficient water supply.